Menumbuhkan Minat Baca Siswa Melalui Kegiatan Literasi di Sekolah - Khasanah, Danisa Wahyu; Dewi, Ainun Niswah Putri Rahmanda; Budiwati, Oktavia Selma (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is motivated by students' interest in reading in Indonesia. Students' interest in reading in Indonesia is still relatively low. Education in Indonesia lags other countries. There are two factors that influence low interest in reading, namely internal factors that come from oneself and external factors that come from outside. This research is a type of qualitative research with a literature study method (library research). The process of collecting data by searching for sources and constructing them from various sources, for example books, articles and research that has already been carried out. The analysis technique used in this research is content analysis. The low interest in reading in Indonesia needs to be addressed, one way is by implementing the School Literacy Movement (GLS). GLS is a government program implemented to foster interest in reading among students in Indonesia. The main aim of GLS is to foster interest in reading widely, so that it is easy to recognize letters or words that are not well understood and increase motivation in the independent learning process. GLS is carried out in three stages, first the habituation stage, the development stage, and the learning stage. There are factors that support and factors that hinder the implementation of the GLS strategy.